A comparative review for hydrogen production from biomass using steam and supercritical water gasification technologies - Wafa A. Aldeeb; Omar A. Algeidi (African Journal of Advanced Pure and Applied Sciences, 2025)
Biomass gasification has emerged as a promising technology for sustainable hydrogen production, offering a renewable pathway to meet global energy demands while reducing greenhouse gas emissions. This review provides an in-depth analysis of biomass gasification technologies, focusing on steam gasification and supercritical water gasification. It critically evaluates the influence of operating conditions, such as temperature, pressure, and feedstock characteristics, on hydrogen yield and syngas quality. The role of advanced catalysts in enhancing process efficiency and mitigating tar formation is also discussed in detail, with emphasis on transition metals, bimetallic catalysts, and novel composite materials. Challenges such as high capital costs, tar management, scalability, and competition with alternative hydrogen production methods are addressed, along with potential technological innovations to overcome these barriers. By integrating recent advancements and identifying critical research gaps, this manuscript aims to guide future studies toward achieving cost-effective and sustainable hydrogen production via biomass gasification. The review underscores the importance of techno-economic analyses, sustainability assessments, and large-scale implementation strategies to ensure the viability of biomass-derived hydrogen as a green energy carrier.